2021
DOI: 10.3892/mmr.2021.12377
|View full text |Cite
|
Sign up to set email alerts
|

Porcine pancreas mesenchymal cell characterization and functional differentiation into insulin‑producing cells in vitro

Abstract: Cell therapy is a promising treatment strategy for patients with type 1 diabetes. Porcine pancreas-derived mesenchymal stromal cells (PMSCs) have emerged as one of the most widely used cell resources owing to their high proliferative capacity and multi-lineage differentiation potential. Although the induction efficiency and insulin production of induced insulin-producing cells (IPCs) derived from PMSCs have been estimated, these have primarily focused on the function of induced cells and alterations in related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Immunofluorescence Analysis of Insulin in the Pancreatic β-Cell of T2DM Mice. Since the previous study reported that insulin is secreted by β-cells in the pancreas, which is one of the most important metabolic hormones to control blood glucose, 38,39 we investigated the ability of insulin secretion and the potential effects of MTNP on pancreatic βcell injury in diabetic mice. Immunofluorescence (IF) analysis was utilized to measure the expression of insulin in the pancreas, in which the anti-insulin antibody was used to determine the insulin expression.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Immunofluorescence Analysis of Insulin in the Pancreatic β-Cell of T2DM Mice. Since the previous study reported that insulin is secreted by β-cells in the pancreas, which is one of the most important metabolic hormones to control blood glucose, 38,39 we investigated the ability of insulin secretion and the potential effects of MTNP on pancreatic βcell injury in diabetic mice. Immunofluorescence (IF) analysis was utilized to measure the expression of insulin in the pancreas, in which the anti-insulin antibody was used to determine the insulin expression.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Insulin is known to be secreted by β-cells in the pancreas and is one of the most important metabolic hormones in the control of blood glucose [ 41 ]. The expression of insulin in the pancreas can be measured using immunofluorescence (ICC) labeling of the insulin in the pancreas (pink fluorescent area in Figure 5 a).…”
Section: Resultsmentioning
confidence: 99%
“…Although an optimal treatment for acute or chronic graft-versus-host disease (GvHD) has not yet been developed, hMSCs have significant therapeutic potential. Since hMSCs promote immunosuppressive and immunomodulatory environments through a number of mechanisms, including protein/peptide/hormone secretion, mitochondrial delivery, and the transfer of exosomes or micelles containing RNA and other molecules, hMSCs are also considered a promising medium for cell therapy against T1D [22][23][24][25][26]. Although pancreatic insulin-producing β-like cells have been generated from MSCs in vitro and transplanted in diabetic animal models, their underlying mechanisms of action have not yet been elucidated [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although pancreatic insulin-producing β-like cells have been generated from MSCs in vitro and transplanted in diabetic animal models, their underlying mechanisms of action have not yet been elucidated [23]. MSCs express chemokine receptors and play an important role in the homing effect [27] as well as in pancreatic regeneration [23,24]. Furthermore, the systemic administration of MSCs in STZ-induced diabetic rats resulted in an increase in β-cell volume [24,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation